ANALISIS INTENSI RUMAH TANGGA DALAM PENGGUNAAN ENERGI HIJAU DI KOTA BATAM - Andina Fasha; Valent Valent; Listia Nurjanah (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the factors influencing household intentions to use green energy in Batam City. The increasing electricity consumption and the impacts of global warming highlight the urgent need for more environmentally friendly energy utilization. This research examines the effects of biospheric value, altruistic value, egoistic value, and environmental self-identity on green attitude as well as intention to use green power. The study employs a quantitative approach using questionnaires distributed to households in Batam City. Data were analyzed using Partial Least Squares Structural Equation Modeling PLS-SEM. The results indicate that egoistic value, altruistic value, biospheric value, and environmental self-identity have significant effects (p-values < 0.05) on both green attitude and intention to use green power. Egoistic value exerts the strongest influence on green attitude, while altruistic value has the strongest influence on intention to use green power. Overall, all variables in this study demonstrate significant effects, indicating that the proposed research model is robust and empirically supported. This study is expected to contribute to the development of research on sustainable energy consumption behavior and serve as a reference for governments and energy providers in promoting the adoption of green energy among the public.